2015
DOI: 10.4103/1947-2714.168660
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer for the internist

Abstract: In the United States, approximately 240,000 men are diagnosed annually with prostate cancer. Although effective treatment options are available for clinically localized cancer, the potential burdensome co-morbidities and attendant healthcare costs from over diagnosis and over treatment have escalated the discussion and controversy regarding appropriate screening, diagnosis, and optimal management of prostate cancer. Although the lifetime risk of developing prostate cancer is approximately 1 in 6 (~16%), the ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 21 publications
0
8
0
1
Order By: Relevance
“…Prostate cancer (PCa) represents the most commonly diagnosed malignancy in men and the second cause of male cancer death worldwide [1, 2]. Substantial evidence suggests that chronic inflammation and angiogenesis contribute to tumour initiation, metastasis, and progression [36].…”
Section: Introductionmentioning
confidence: 99%
“…Prostate cancer (PCa) represents the most commonly diagnosed malignancy in men and the second cause of male cancer death worldwide [1, 2]. Substantial evidence suggests that chronic inflammation and angiogenesis contribute to tumour initiation, metastasis, and progression [36].…”
Section: Introductionmentioning
confidence: 99%
“…Prostate cancer (PCa) is a most frequently occurring malignancy among older men [1, 2]. Prostate tumors are usually indolent, but a considerable number of tumors are highly aggressive and often metastasize to bones and other organs, leading to high morbidity and mortality [3, 4]. In addition, PCa is typically marked by a high recurrence rates, whereby about 40% of local PCa cases recur after initial treatment, and the tumor progresses to hormone refractory/castration resistance stage is basically untreatable [5, 6].…”
Section: Introductionmentioning
confidence: 99%
“…They can also occur when guidelines from outside organizations diverge, as with breast and prostate cancer screening recommendations. 10,11 Interviewees reported that their quality improvement committees, sometimes in combination with compensation committees, work to understand the differences, better align metrics across payer contracts when possible, and identify internal organization-wide metrics.…”
Section: Evaluation Of Preventive Services and Broader Performance Momentioning
confidence: 99%